Human dimensions in shellcraft: tool ownership differentiates taxa utilised and products produced - Militz, Thane A.; Simard, Nittya S. M.; Kinch, Jeff; Southgate, Paul C. (Frontiers in Marine Science, 2024)
Throughout the Pacific Islands, shellcraft has begun to feature prominently in development intervention which aims to generate positive livelihood outcomes for coastal communities. This activity often involves the post-harvest processing of natural assets, namely shells and skeletal remains of marine taxa, into jewellery by individuals or small-sized enterprises. To foster participation in shellcraft, development intervention commonly involves gifting or subsidising physical assets. Yet knowledge of the natural (i.e., taxa) and physical (i.e., tools) assets required for shellcraft remains scant. An understanding of human dimensions in shellcraft pertaining to patterns in asset use, such as how tool ownership differentiates taxa utilised and products produced, is important for determining if access to a specific tool is necessary, or an encumbrance, for achieving a desired outcome. In this study, we identified tools used and variation in tool ownership among artisans engaged in shellcraft to afford an accurate and realistic understanding of the tools required to participate in this activity. We then evaluate how ownership of a specific tool or type of tool differentiates both taxa utilisation and product production for shellcraft. Results indicate ownership of neither all nor any specific tool was required to participate in shellcraft, with artisans typically owning a unique combination of tools. Furthermore, results identified that some specific tools were critical for affecting the attractiveness of utilising certain taxa or producing certain products. Implications of the significant relationships between specific tools and certain taxa or products are discussed in the context of development intervention and commonly articulated theories of change where shellcraft is linked to subsistence fishing, aquaculture, or tourism.